2008
DOI: 10.1103/physrevb.78.144514
|View full text |Cite
|
Sign up to set email alerts
|

Experimental consequences of thes-wavecos(kx)cos(ky

Abstract: The experimental consequences of different order parameters in iron-based superconductors are theoretically analyzed. We consider both nodeless and nodal order parameters, with an emphasis on the cos(kx) · cos(ky) nodeless order parameter recently derived by two of us 1 . We analyze the effect of this order parameter on the spectral function, density of states, tunneling differential conductance, penetration depth, and the NMR spin relaxation time. This extended s-wave symmetry has line-zeroes in between the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 61 publications
5
107
2
Order By: Relevance
“…Theoretical results indicate the presence of s x 2 y 2 ∼ cos(k x ) · cos(k y ) (also called s ± ) pairing symmetry in FeSC [37][38][39][40][41][42][43]. In this case the OP exhibits a sign reversal between the hole pockets and electron pockets (Fig.…”
Section: Minimization Of Free Energymentioning
confidence: 99%
“…Theoretical results indicate the presence of s x 2 y 2 ∼ cos(k x ) · cos(k y ) (also called s ± ) pairing symmetry in FeSC [37][38][39][40][41][42][43]. In this case the OP exhibits a sign reversal between the hole pockets and electron pockets (Fig.…”
Section: Minimization Of Free Energymentioning
confidence: 99%
“…Two of us showed that the pairing symmetry is determined mainly by the next-nearest-neighbor (NNN) antiferromagnetic (AFM) exchange coupling J 2 together with a renormalized narrow band width [11,46]. The superconducting gap is close to a cosðk x Þ cosðk y Þ form in momentum space.…”
Section: Introductionmentioning
confidence: 99%
“…In many iron pnictides, ARPES studies shows multiple isotropic gaps with s-wave pairing symmetry [29,30] , and an s ± pairing has been proposed due to interband transitions [31,32] . The coherence peak for the s ± superconductivity may be suppressed by interband impurity scatterings [33][34][35][36][37] . In heavily hole-doped KFe 2 As 2 and the isovalent-doped BaFe 2 As 2-x P x , however, superconducting gaps with line nodes were proposed [7,38] , to account for the absence of the coherence peak [7] .…”
mentioning
confidence: 99%